2015
DOI: 10.1051/radiopro/2015003
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the radiation dose to the eye lens region during CT brain examination: the potential beneficial effect of the combined use of bolus and a bismuth shield

Abstract: -Objective:Computed Tomography (CT) is the leading contributor to medical exposure to ionizing radiation. Although the use of CT brain scans for patients with head injuries and convulsions has shown a tremendous growth, it has raised substantial concerns in the general public because of the risk of radiation-induced cataracts: the current available strategies to reduce the radiation dose to the eye lens region are limited. Therefore, the present research project was initiated with the aim of evaluating the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Of the trials which utilised a degree of gantry tilt as a component of their reference scanning technique, doses were significantly lower overall, mainly where alignment could be achieved along the supraorbital margin such that the lenses of the eyes were no longer within the primary irradiation beam. However, of these studies, the majority of those who were able to achieve adequate alignment were phantom trials . While the use of anthropomorphic phantoms in such studies allows precise documentation of absorbed dose, variations in patient size and position are not able to be taken into account.…”
Section: Radiation Dose To the Lens Of The Eye During Ct Scans Of Thementioning
confidence: 99%
See 2 more Smart Citations
“…Of the trials which utilised a degree of gantry tilt as a component of their reference scanning technique, doses were significantly lower overall, mainly where alignment could be achieved along the supraorbital margin such that the lenses of the eyes were no longer within the primary irradiation beam. However, of these studies, the majority of those who were able to achieve adequate alignment were phantom trials . While the use of anthropomorphic phantoms in such studies allows precise documentation of absorbed dose, variations in patient size and position are not able to be taken into account.…”
Section: Radiation Dose To the Lens Of The Eye During Ct Scans Of Thementioning
confidence: 99%
“…The number and placement of dosimeters differ from each trial, which could affect the consistency and reproducibility of the results with only one or two devices. As well as this, the inclusion of the dosimeter in the scout images, as opposed to being attached after the scout images have been taken, could have implications on the end dose; however, admittedly its contribution would likely be relatively low.…”
Section: Radiation Dose To the Lens Of The Eye During Ct Scans Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown a drift in CT numbers between 50 and 65%. 25,26,28 There are also many studies that support the use of bismuth, suggesting no significant impact on image quality. 19,20,28 Where as these studies agree that streak artifacts disrupt image quality, the majority suggest that by creating a small gap between the eye lens and the shield, artifacts can be reduced to an acceptable diagnostic level.…”
Section: 21mentioning
confidence: 99%
“…19,20,28 Where as these studies agree that streak artifacts disrupt image quality, the majority suggest that by creating a small gap between the eye lens and the shield, artifacts can be reduced to an acceptable diagnostic level. 9,17,19,24,26 Our study by Raissaki et al 24 reduced artifacts to a negligible level by elevating the shield from the eyes using folded gauzes. Distances of 5, 10 and 20 millimeters were evaluated and found to reduce artifacts resulting in only slight decreases to dose reductions.…”
Section: 21mentioning
confidence: 99%